The role of oxidative stress in the pathophysiology of gestational diabetes mellitus - Lappas, Martha (2011)
Normal human pregnancy is considered a state of enhanced oxidative stress. In pregnancy, it plays important roles in embryo development, implantation, placental development and function, fetal development, and labor. However, pathologic pregnancies, including gestational diabetes mellitus (GDM), are associated with a heightened level of oxidative stress, owing to both overproduction of free radicals and/or a defect in the antioxidant defenses. This has important implications on the mother, placental function, and fetal well-being. Animal models of diabetes have confirmed the important role of oxidative stress in the etiology of congenital malformations; the relative immaturity of the antioxidant system facilitates the exposure of embryos and fetuses to the damaging effects of oxidative stress. Of note, there are only a few clinical studies evaluating the potential beneficial effects of antioxidants in GDM. Thus, whether or not increased antioxidant intake can reduce the complications of GDM in both mother and fetus needs to be explored. This review provides an overview and updated data on our current understanding of the complications associated with oxidative changes in GDM.